2016
DOI: 10.5114/aic.2016.63632
|View full text |Cite
|
Sign up to set email alerts
|

Patient profile and periprocedural outcomes of bioresorbable vascular scaffold implantation in comparison with drug-eluting and bare-metal stent implantation. Experience from ORPKI Polish National Registry 2014–2015

Abstract: IntroductionThere are limited data on the comparison of bioresorbable vascular scaffold (BVS) and drug-eluting stent (DES)/bare-metal stent (BMS) implantation in an unselected population of patients with coronary artery disease.AimTo compare the periprocedural outcomes and patient profile of BVS and DES/BMS implantation in an all-comer population from the ORPKI Polish National Registry.Material and methodsA total of 141,324 consecutive patients from 151 invasive cardiology centers in Poland were included in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
8
0
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
8

Relationship

4
4

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 32 publications
(58 reference statements)
1
8
0
1
Order By: Relevance
“…A higher prevalence of stable angina and lower rate of multi-vessel disease were also reported by Rzeszutko et al [ 11 ]. Similarly, the main periprocedural major adverse event was coronary artery perforation.…”
Section: Discussionsupporting
confidence: 64%
“…A higher prevalence of stable angina and lower rate of multi-vessel disease were also reported by Rzeszutko et al [ 11 ]. Similarly, the main periprocedural major adverse event was coronary artery perforation.…”
Section: Discussionsupporting
confidence: 64%
“…Bioresorbable vascular scaffolds is relatively new in interventional cardiology. First generation BVS in simple de-novo lesions has been proven to be almost as good as DES with comparable MACE event rates (ABSORB, ABSORB II) and in all comer registries as in the retrospective registry GHOST-EU, the target lesion failure rate (TLF) at 1 year was very acceptable given the lesion and patient complexity; however, an increase in early ST was noted [ 10 , 11 ]. The ABSORB III trial demonstrated that the scaffold was non-inferior to the Xience stent with respect to target lesion failure at 1 year [ 12 ].…”
Section: Discussionmentioning
confidence: 99%
“…Previously, published data from the ORPKI registry revealed an increased number of CAPs in patients with PCI and BVS in comparison to those with DES/BMS. This was explained by the preparation of the lesion for stent implantation . Previously published studies revealed that among predictors of in‐hospital MACE we may find peripheral artery disease, Dialysis, type C lesion and radial access .…”
Section: Discussionmentioning
confidence: 99%